The Japanese ninja surprise - Pennypacker, Sara, 1951-; Brown, Jeff, 1926-2003.; Pamintuan, Macky (New York : Scholastic, 2009)
Flat Stanley mails himself to Japan to visit his hero, martial arts movie star Oda Nobu, and becomes his personal ninja.
Includes an excerpt from: The intrepid Canadian expedition.
b
b
Keywords: Ninja -- Juvenile fiction; Martial arts -- Juvenile fiction; Actors -- Juvenile fiction; Ninja -- Fiction; Martial arts -- Fiction; Actors and actresses -- Fiction; Voyages and travels -- Fiction; Flat Stanley (Fictitious character) -- Fiction; Japan -- Juvenile fiction; Japan -- Fiction